The Extent of Civil Society Participation in Local Governance in Iligan City, 2004-2007 - Lumayag-Codilla, Elizabeth (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper verifies the extent of civil society organizations' participation in local governance. Specifically, it aims to examine their attributes; investigate the extent of their participation in political and administrative governance; explore the significant difference in the extent of their participation when grouped according to their attributes; delve into the best practices; and identify the problems that they experienced while participating in local governance. This paper employed a triangulation of methods of data gathering: a survey; one·on·one in·depth interview; and focus group discussion (FGD). Secondary data, particularly on the mechanics of accrediting CSOs, were obtained from the Department of Interior and Local Government and Sangguniang Panlungsod. There was a total of 32 survey respondents, ten (10) key informants and 20 FGD participants constituting the data sources of this research.The findings show that the CSOs are legitimate and functional. The extent of their participation in planning socio-economic projects, peace, order, and public safety and in advertising bids is limited; while the extent of their participation is nil in planning and recommending changes in the names of public schools and in creating committees to advise local health agencies on health matters.